Evaluating the Potential of Container-Based Sanitation - World Bank (World Bank, Washington, DC, 2019)
In the face of urbanization, alternative approaches are needed to deliver adequate and inclusive sanitation services across the full sanitation service chain. Container-based sanitation (CBS) consists of an end-to-end service—that is, one provided along the whole sanitation service chain—that collects excreta hygienically from toilets designed with sealable, removable containers and strives to ensure that the excreta is safely treated, disposed of, and reused. This report builds on four case studies (SOIL – Haiti, x-runner – Peru, Clean Team – Ghana, Sanergy – Kenya) to assess the role CBS can play in a portfolio of solutions for citywide inclusive sanitation (CWIS) services. The authors conclude that CBS approaches should be part of the CWIS portfolio of solutions, especially for poor urban populations for whom alternative on-site or sewer-based sanitation services might not be appropriate. Customer satisfaction with existing services is high and services provided by existing CBS providers are considered safe but have some areas for improvement. While the proportion of total CBS service costs covered by revenues is still small, CBS services are considered to be priced similarly to the main sanitation alternatives in their service areas. Recommendations include adopting a conducive policy and regulatory environment and exploring ways to ensure that CBS services are sustainably financed. The report also identifies areas for further analysis.